PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA BKD KABUPATEN LAHAT - Kusuma, Aditya (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2007)
The reasearch aims at figuring out work environment, personnel performance and the influence of work environment on personnel performance at Lahat District Civil Service Bureau. Based on preliminary research, the writer identified several factors leading to low personnel performance, the most likely of which is the less favorable work environment. The research result shows that the work environment at Lahat District Civil Service Bureau needs to be optimized through maintaining, upgrading, and reorganizing work facilities and infrastructure in ergonomic ways.